2015
DOI: 10.1515/afe-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Coefficient in the Zinc Coating Shaped on the Surface of Cast Iron and Steel Alloys

Abstract: The article presents the method to assess the diffusion coefficient D in the sub-layer of intermetallic phases formed during hot-dip galvanizing “Armco” iron and ductile cast iron EN-GJS-500-7. Hot-dip galvanizing is one of the most popular forms of long-term protection of Fe-C alloys against corrosion. The process for producing a protective layer of sufficient quality is closely related to diffusion of atoms of zinc and iron. The simulation consist in performed a hot-dip galvanizing in laboratory condition ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Gogola et al [18] reported more specifically on the phase evaluation of galvanised coatings on a high-carbon steel with the emphasis on the coating morphology. It was interesting to find a hot-dip coating microstructure with similar features between a high-carbon steel [18] and ductile iron castings with over 3.0 wt.% of C [19,20]. However, none of the studied literature sources investigated the behaviour of Zn-based coatings on medium-to-highcarbon steels after exposure to over 600 • C.…”
Section: Introductionmentioning
confidence: 99%
“…Gogola et al [18] reported more specifically on the phase evaluation of galvanised coatings on a high-carbon steel with the emphasis on the coating morphology. It was interesting to find a hot-dip coating microstructure with similar features between a high-carbon steel [18] and ductile iron castings with over 3.0 wt.% of C [19,20]. However, none of the studied literature sources investigated the behaviour of Zn-based coatings on medium-to-highcarbon steels after exposure to over 600 • C.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all high-chromium cast iron utilized commonly in the abrasive wear conditions are the hypoeutectic alloys with the content of 10 -30% Cr and 2 -3.5% C. Their wear resistance and mechanical properties depend on the type, morphology, and volume fraction of carbides in the structure and on the matrix characteristics within which they are embedded [1,2,3,4]. The increase in the carbon and chromium contents increases the amount of the carbides, and therefore, the wear resistance improves, while toughness and the fracture resistance of castings' material are decreased.…”
Section: Introductionmentioning
confidence: 99%
“…The methods to achieve the fracture resistance can be different and, unless they are not mutually exclusive, they can be combined. The researches have indicated that to use these irons more extensively there is desired to focus on the effect of microalloying and inoculation of molten metal [1,3], possibility to modify the service properties of material using a heat treatment [1,2], and the method of hardening of the iron's matrix under the local plastic strain [1,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation